The Euro and the CFA Franc: Evidence of sectoral trade effects - Inmaculada Martínez-Zarzoso (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
This paper estimates a gravity model of trade to evaluate the trade effects of the Euro on sectoral trade within the Euro Zone, the CFA Franc Zone and between the Eurozone and the CFA Franc Zone, when CFA countries acquired fixed rates against the non-francophone Eurozone members. The formation of the Eurozone provides a quasi-natural experiment to estimate the effects on trade of fixed exchange rates, since the change in exchange rate regime for CFA countries with all Eurozone countries but France was not trade related. This is tested using sectoral trade data for 128 countries over the period 1995-2009 and validated using a larger sample of 180 countries over the period 1973 -2013. The main departure from Frankel (2008), is the use of sectoral trade and the inclusion of bilateral-sectoral fixed effects as well as controls for multilateral resistance, namely time varying country-fixed-effects for exporters and importers, in the gravity model specification. The main results indicate that the introduction of the Euro is generally not associated with positive effects for average trade flows between the CFA Franc Zone and other Eurozone countries. However, the results differ by sector and we find that agricultural (homogeneous products) exports from CFA countries to Euro adopters increased by almost fifty (thirty) percent after the euro adoption.
Keywords: F10; F14; 330; CFA; Euro Effect; Bilateral Trade; Panel Data